Developing an Integrated Industrialised Building system (IBS) maturity model: a hybrid model with RIGGS'S OMAX - Lee, Chia Kuang (2017)
Industrialized Building System (IBS) is a form of construction with focused processes comprise of methods, products and a set of connected components which works together to achieve objectives. Malaysian construction industry is among the main contributor towards the development of the country. To ensure vitality of construction performance, utilization and application of IBS is the right system to shift to from current conventional construction method. Adaptability of IBS in Malaysian’s construction industry is very low due to various limitations and barriers. From a total of 110 articles reviewed in this paper, 8 factors were highly mentioned which are reduced workplace accidents, transportation and logistics, adequate knowledge and expertise, reduction in environmental degradation, management factor, integration of process and training, communication and financial status. These are all the barriers and limitations that impede the development and adaptability of IBS in Malaysia’s construction industry that can also be used as crucial factors that can also significantly influence IBS project performance.